Students’ Knowledge and Attitudes in Behaviors about Sustainable Development Goals (SDGs) In Lagos State University, Lagos Nigeria - Ogundele, Fatai Olakunle; Olatunji-Bello, Ibiyemi Ibilola; Adeneye, Adejuwon Adewale (Journal of Sustainability Perspectives, 2024)
The present study examined students’ knowledge and attitudes in behavior about the United Nations Sustainable Development Goals (SDGs) at Lagos State University, Lagos State, Nigeria. The data for the study were extracted and analyzed from the 353 copies of structured questionnaires that were self-administered to students across the ten (10) faculties. Data was analyzed using simple percentages, tables, One-Way Analysis of Variance (ANOVA), and logistic regression analysis. Results showed that a good percentage (77.1%) of the respondents had knowledge of and were aware of the term SDGs. Social media (33.1%), lectures (14.4%), and television (12.5%) were the prominent sources of SDGs awareness by the respondents who claimed they were aware of the term SDGs. The level of awareness of the various SDGs also varied among the students with most students being aware of 14 of the SDGs (77%), while the remaining (23%) claimed they were not familiar with three goals (9, 12, and 17). The result of the awareness further showed that among the SDGs they claimed they were aware of (91%) were for SDG 1 (NO POVERTY), while, the percentage of the level of awareness for the remaining varied from 1.1% to 13.5%. The students displayed behavioral support toward the actualization of sustainable development goals by encouraging a sustainable energy approach, encouraging sustainable consumption patterns, and discouraging biodiversity loss through their behaviors. Based on these findings, it is strongly recommended that the universities in Nigeria revise and incorporate the teaching of the SDGs into their academic curricula. This step will afford the students adequate knowledge about the UN SDGs and how these can be achieved and sustained.